One HACCP, two approaches: experiences with and perceptions of the Hazard Analysis and Critical Control Points (HACCP) food safety management systems in the US and the EU - Hyde, Richard; Hoflund, A. Bryce; Pautz, Michelle C. (SAGE, 2014)
This paper explores the differences in the use of the Hazard Analysis Critical Control Point (HACCP) system to manage food safety risks in the food chain from farm to fork in the EU and the US. In particular, this paper investigates the current uses and potential expansion of HACCP as a mechanism for the delivery of safe agricultural products, particularly safe produce. It considers not only whether HACCP systems are the best mode of governance for delivering safe food, and describes why HACCP has achieved an important role in the regulatory framework that governs food safety, but asks why this role is different in the EU and US. Within the EU, HACCP is compulsory at all stages of the food chain other than primary production, whereas the mandatory use of HACCP in the US is less widespread. However, the empirical work found that HACCP is being used by businesses in both the EU and US as a basis for organizing their business, even when not required by regulation. Using data derived from semi-structured interviews with regulatory actors in the EU and US, this paper argues that the different approach to HACCP is a result of differing ideas about the role that it plays in the governance of food safety, and the different concepts of the role of regulation in securing safe food. Finally, the paper explores the difficulties of utilizing HACCP to manage produce safety risks, and raises further challenges that must be met in order to ensure that HACCP can successfully fulfill its potential as a governance mechanism.